2010
DOI: 10.1007/s00464-010-1350-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intraoperative breaks on mental and somatic operator fatigue: a randomized clinical trial

Abstract: Our data support the idea that work breaks during complex laparoscopic surgery can reduce psychological stress and preserve performance without prolongation of the operation time compared with the traditional work scheme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
90
2
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(99 citation statements)
references
References 11 publications
4
90
2
3
Order By: Relevance
“…A study found that scheduled intraoperative breaks reduced surgeons' cortisol levels by 22%, without prolonging the operation. 26 A systematic review looking at residents' health found 2 studies on protected sleep time to reduce residents' fatigue. 27 Further studies on scheduled breaks and protected sleep time with a focus on how surgeons' stress can be reduced are needed.…”
Section: Resultsmentioning
confidence: 99%
“…A study found that scheduled intraoperative breaks reduced surgeons' cortisol levels by 22%, without prolonging the operation. 26 A systematic review looking at residents' health found 2 studies on protected sleep time to reduce residents' fatigue. 27 Further studies on scheduled breaks and protected sleep time with a focus on how surgeons' stress can be reduced are needed.…”
Section: Resultsmentioning
confidence: 99%
“…Haynes et al retrospectively reviewed 6371 general surgical procedures and found the highest rate of complications in those who had been performed by individuals on call in the last 24 h [22]. Engleman et al evaluated the impact of intraoperative 5 min breaks every half an hour (similar to in air traffic controllers) during complex laparoscopic surgery and demonstrated that this did not prolong operations, reduced cortisol levels and led to fewer intraoperative adverse events [23].…”
Section: What Is Happening In the Context Of Cardiothoracic Surgery?mentioning
confidence: 99%
“…This study does not assess skills per se, yet experience would influence the psychophysical score. Engelmann et al showed that breaks during complex laparoscopic surgery reduced psychological stress maintaining efficiency without prolonging operating time [5]. In athletics, Borg CR10 is used to score and plan the methodology of training [15].…”
Section: Discussionmentioning
confidence: 99%